Exploring the Impact of Decision-Variables on Enterprise Digital Transformation - Fernandes, Anil Perim (Global journal of Business and Integral Security, 2025)
Every Enterprise's Digital Transformation (EDT) is unique and is influenced by its organisational environment. The execution and successful implementation of such a transformation depends on numerous factors affecting the desired outcomes. These decision factors or variables can significantly impact Enterprise Digital Vision's (EDV) overall accomplishment. By definition, the variables refer to any factors, such as resources, skills, enterprise digital strategy, governance, schedule and budget, which may prevent a transformation in achieving its envisioned goals. Successful execution and implementation of an Enterprise Digital Transformation relies on effective identification and management of the decision variables through strategic and tactical interventions. While the strategic vision provides a global enterprise view and the overall execution & implementation strategy, tactical interventions will ensure timely decision-making and risk mitigation. Purpose: This research explores and analyses the influence of ‘Enterprise Architecture '-focused decision variables on ‘Enterprise Digital Transformation’. Methods: The research examines various decision variables gathered via leadership surveys, interviews, and literature reviews. It analyses the effectiveness of strategic and tactical interventions in managing these variables and their influence on program success. In this research study, a specific focus has been placed on Enterprise Architecture as a critical decision variable impacting EDT. Results: The study finds that unaddressed decision variables related to enterprise architecture can significantly hinder an EDT program’s progress. Strategic planning offers a high-level approach to program execution, while tactical planning enables timely interventions and risk mitigation. Both are essential for managing decision variables and ensuring EDT goals are met. Conclusions: This research study was initiated with the question of why enterprise digital transformations had a high failure rate. During the literature study, 23 key variables were identified as primary decision variables that impact EDT outcomes most. The scope of this study was limited to understanding the effects of variables related to ‘Enterprise Architecture’. The primary focus was enterprise strategy, discovery, governance & change management. The findings were further analysed and validated by the survey results. The respondents were asked about their view of the challenges that impacted the EDT initiative. To avoid any bias, the respondents were presented with various options. The results highlighted that Enterprise Architecture variables, Skills gap & availability of talent were significant factors that impacted EDT outcomes. Leadership across enterprises acknowledged that effective management of decision variables, especially Enterprise Architecture, is crucial for the success of EDT programs. Organisations that identify and address these factors early, through strategic and tactical planning, are better positioned to achieve their digital transformation objectives. The research emphasises the need to acknowledge and govern the 23 identified decision variables to ensure successful Enterprise Digital Transformation (EDT).